Analisis Kualitas Pelayanan Jasa Perbankan Syariah Dengan Metode Fuzzy-Service Quality Studi Pada Bank Syariah Indonesia Kantor Cabang Pembantu Kisaran - Fahmiatul Aulia Pangaribuan; Ahmad Amin Dalimunthe; Muhammad Ikhsan Harahap (AGHNIYA : Jurnal Ekonomi Islam, 2023)
This study aims to see and analyze how the service quality at Bank Syariah Indonesia KCP Kisaran uses the Fuzzy-Service Quality method. The method used in this study is a qualitative approach. The sampling technique is random sampling. The sample used was 100 people with a Likert scale-based questionnaire for data collection. Based on the results of defuzzification calculations, the highest perceived value of service quality for BSI Sub-Branch Offices is 76,5. For defuzzification calculations, it is known that the highest expectation value of BSI service quality is 91,25. Meanwhile, the gap between perceptions and expectations shows a negative value, namely -1,64 or not 1, meaning that what the customer expects is not fully in accordance with what is received by Bank Syariah Indonesia customers at the Kisaran Sub-Branch Office.